An empirical study on ERP-driven innovation in Taiwan. (24th February 2005) - Wu, Jen-Her; Wang, Yu-Min; Lu, Iuan-Yuan
This study investigates the relationship between ERP (Enterprise Resource Planning)-driven innovation outcomes across different industry sectors (i.e., electronics and science (ES) industry vs. traditional industry) and ERP packages (i.e., domestic vs. foreign). The results indicate that the ERP penetration rate for the ES industry is significantly higher than that for traditional industry. The ES industry prefers foreign ERP packages and implementing domestic ERP receives higher user satisfaction rate (i.e., ERP innovation success). However, the degree of innovation success is low for all industry sectors and ERP packages. Several implication suggestions and research issues based on the findings from this research are proposed for practitioners and researchers.